Protein interaction cloning in yeast: identification of mammalian proteins that react with the leucine zipper of Jun. - Chevray, P M (1992)
To identify proteins that interact with Jun or Fos we have used the protein interaction cloning system developed by S. Fields and O.-K. Song [(1989) Nature (London) 340, 245-246] to clone mammalian cDNAs encoding polypeptides that interact with the dimerization and DNA-binding motif (bZIP; basic domain leucine zipper motif) of Jun. For this purpose, yeast cells lacking GAL4 activity but expressing a GAL4 DNA-binding domain-Jun bZIP fusion protein were transformed with a mouse embryo cDNA plasmid library in which the cDNA was joined to a gene segment encoding the GAL4 transcriptional activation domain. Several transformants exhibiting GAL4 activity were identified and shown to harbor plasmids encoding polypeptides predicted to form coiled-coil structures with Jun and/or Fos. One of these is a bZIP protein of the ATF/CREB protein family--probably the murine homolog of TAXREB67. Two others encode polypeptides with predicted potential to form coiled-coil structures, and seven other isolates encode segments of alpha- or beta-tropomyosin, classical coiled-coil proteins. The tropomyosin polypeptides were found to interact in the yeast assay system with the bZIP region of Jun but not with the bZIP region of Fos. Our results illustrate the range of protein interaction cloning for discovering proteins that bind to a given target polypeptide.